2020
DOI: 10.15330/pcss.21.3.552-559
|View full text |Cite
|
Sign up to set email alerts
|

Alternative fuels from vegetable oils: innovative methods and technologies of production and usage

Abstract: Traditional methods of biofuel production using vegetable oils and aliphatic alcohols have a number of disadvantages. A new method of transesterification of vegetable oils with alkyl acetates because they act as promoters of diesel fuel combustion. A method of improving both technology of alcoholysis and esterolysis by modifying the temperature range is proposed. Chemical and technological bases of two-stage process of vegetable oil transesterification are developed. In the first stage, the oils are treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Of particular importance is the coverage of the results of the study of the influence of surface activity (SA) of lubricants, in particular the values of dipole moments of base oil molecules, their polarity and polarizability on the processes of their hemisorption and tribochemical reactions [10]. It is shown that the level of polarity and ability to polarize base oils significantly affects a number of surface phenomena in nanolayers of friction metals, primarily the density of dislocations and plastic deformation of surfaces, as well as their deformation hardening and as a consequence on energy and material friction criteria.…”
Section: Problem Analysismentioning
confidence: 99%
“…Of particular importance is the coverage of the results of the study of the influence of surface activity (SA) of lubricants, in particular the values of dipole moments of base oil molecules, their polarity and polarizability on the processes of their hemisorption and tribochemical reactions [10]. It is shown that the level of polarity and ability to polarize base oils significantly affects a number of surface phenomena in nanolayers of friction metals, primarily the density of dislocations and plastic deformation of surfaces, as well as their deformation hardening and as a consequence on energy and material friction criteria.…”
Section: Problem Analysismentioning
confidence: 99%